Flocculation model applied to adjust operating conditions as flow changes - Moruzzi, Rodrigo Braga [UNESP]; Manetta, Lívia Savioli [UNESP]; Oliveira, Samuel Conceição [UNESP] (Elsevier, 2017)
Higher flows in the flocculation stage of water and wastewater treatment systems can be dealt with by adapting the operating conditions. This study investigates the changes required to maintain the flocculation efficiency. The present study developed a mathematical model that assimilates particle ratio and shear rate with particle aggregation/breakage kinetics. The model allows determining how higher flow rates may respond under new flocculation conditions. The kinetic coefficients of the model were derived from literature sources. The mathematical model enables selecting the most appropriate combinations of operating variables in order to produce specified efficiency ranges. Due to the number of operating variables, the number of possible solutions to the mathematical model may be very large. Therefore, an important result is that the model can select 0.1%–1.9% of the possible combinations in operating variables, thus minimizing the experimental effort required to verify the response in terms of operation changes.
Keywords: Flocculation process; Mathematical model; Water treatment